Memperkuat Komitmen Organisasional: Peran Budaya Organisasi, Keadilan Distributif dan Keadilan Prosedural - Ignatius Soni Kurniawan Soni; Andre Rifky Prasetyo (Jurnal Manajemen, 2022)
This study aims to determine the effect of organizational culture, distributive justice, and procedural justice on organizational commitment. The population used in this study were employees of Bento Kopi Yogyakarta, the sampling technique used in this study was accidental sampling. The basis of this research is the existence of turnover and the level of employee absenteeism that goes up and down and of the workers are part-time workers. Data were taken using a questionnaire on 95 respondents and processed using multiple linear regression analysis. The results in this study state that organizational culture, distributive justice, and procedural justice have a positive and significant effect on organizational commitment. The findings imply that company leaders can encourage increased organizational commitment through evaluation of items from organizational culture, distributive justice, and procedural justice which are still low which have been mentioned in the discussion section. Keywords: Organizational Culture; Distributive Justice; Procedural Justice; and Organizational Commitment.